f ( n ) = m = 1 ∑ n m 2 ( m n )
If the value of f ( 2 0 1 6 ) can be expressed as A ( A + 1 ) 2 B , where A and B are positive integers, find A + B .
Notation: ( N M ) denotes the binomial coefficient , ( N M ) = N ! ( M − N ) ! M ! .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( x + 1 ) n = C 0 n + C 1 n x + C 2 n x 2 + C 3 n x 3 + ⋯ + C n − 1 n x n − 1 + C n n x n
Differentiate both sides w . r . t . x :
n ( x + 1 ) n − 1 = C 1 n + 2 C 2 n x + 3 C 3 n x 2 + ⋯ + ( n − 1 ) C n − 1 n x n − 2 + n C n n x n − 1
Multiply both sides with x :
n x ( x + 1 ) n − 1 = C 1 n x + 2 C 2 n x 2 + 3 C 3 n x 3 + ⋯ + ( n − 1 ) C n − 1 n x n − 1 + n C n n x n
Differentiate both sides w . r . t . x :
n ( x ( n − 1 ) ( x + 1 ) n − 2 + ( x + 1 ) n − 1 ) = C 1 n + 2 2 C 2 n x + 3 2 C 3 n x 2 + ⋯ + ( n − 1 ) 2 C n − 1 n x n − 2 + n 2 C n n x n − 1
Put x = 1 :
n ( ( n − 1 ) ( 2 ) n − 2 + ( 2 ) n − 1 ) = C 1 n + 2 2 C 2 n + 3 2 C 3 n + ⋯ + ( n − 1 ) 2 C n − 1 n + n 2 C n n = f ( n )
⇒ f ( 2 0 1 6 ) = 2 0 1 6 ( ( 2 0 1 5 ) 2 2 0 1 4 + 2 2 0 1 5 ) = 2 0 1 6 ⋅ 2 0 1 7 ⋅ 2 2 0 1 4
⇒ A = 2 0 1 6 , B = 2 0 1 4
A + B = 2 0 1 6 + 2 0 1 4 = 4 0 3 0 .
Note that ( m − 1 n − 1 ) ( m n ) = m n and m = 0 ∑ n ( m n ) = 2 n .
m = 1 ∑ n m 2 ( m n ) = n m = 1 ∑ n ( m − 1 + 1 ) ( m − 1 n − 1 ) n { m = 1 ∑ n ( m − 1 ) ( m − 1 n − 1 ) + m = 1 ∑ n ( m − 1 n − 1 ) } n { ( n − 1 ) m = 2 ∑ n ( m − 2 n − 2 ) + 2 n − 1 } n { ( n − 1 ) 2 n − 2 + 2 n − 1 } = n ( n + 1 ) 2 n − 2
Genius Solution
@Akshat Sharda i also did same as this .. btw nice solution .. +1
I will prove that f ( n ) = m = 1 ∑ n m 2 ( m n ) = n ( n + 1 ) 2 n − 2 by applying the binomial identity j = 0 ∑ k ( j k ) = 2 k repeatedly.
f ( n ) = = = m = 1 ∑ n m 2 ( m n ) = 1 2 ( 1 n ) + m = 2 ∑ n m 2 ( m n ) n + m = 2 ∑ n [ m ( m − 1 ) + m ] ( m n ) n + : = I m = 2 ∑ n [ m ( m − 1 ) ( m n ) ] + : = J m = 2 ∑ n [ m ( m n ) ]
Let's solve for I and J separately.
For m ≥ 2 , m ( n − 1 ) ( m n ) = = m ( m − 1 ) ( n − m ) ! m ! n ! = m ( m − 1 ) ( n − m ) ! m ( m − 1 ) ( m − 2 ) ! n ! ( n − m ) ! ( m − 2 ) ! n ! = n ( n − 1 ) ( m − 2 n − 2 ) .
Similarly, for m ≥ 1 , m ( m n ) = n ( m − 1 n − 1 ) .
Hence, I = n ( n − 1 ) m = 2 ∑ n ( m − 2 n − 2 ) = n ( n − 1 ) 2 n − 2 and J = n m = 2 ∑ n ( m − 1 n − 1 ) = n ( 2 n − 1 − 1 ) .
By substituting them into f ( n ) and simplify, we will obtain the desired result f ( n ) = m = 1 ∑ n m 2 ( m n ) = n ( n + 1 ) 2 n − 2 .
With f ( 2 0 1 6 ) = 2 0 1 6 × 2 0 1 7 × 2 2 0 1 4 , our answer is A + B = 2 0 1 6 + 2 0 1 4 = 4 0 3 0 .
Food for thought: Can we solve this via induction ? If yes, is it easier or harder to solve via induction?
I will be using s(m=1, n): instead of the epsilon and b(n, m) instead of the regular binomial notation both because I am too lazy to actually learn how to write proper notation here. Anyways, we have f(n)=s(m=1, n):m m n!/((m)! (n-m)!)=s(m=1, n):m n!/((m-1)! (n-m)!)=s(m=1, n):n m (n-1)!/((m-1)!(n-m)!)=n (s(m=1, n):m b(n-1, m-1)) the trick is recognising that for every iteration, we are just starting a new series b(n-1, m-1) without the previous terms as increasing m is the same as simply adding a new copy of the binomial coefficient in the sum, a full binomial series will equate to 2^(n-1) by 2^a=(1+1)^a=s(j=0, a):b(a, j) so we have (taking into account the terms not included in each new case of the series in the sum) f(n)=n ((s(m=1, n):2^(n-1))-(s(m=1, n-1):s(h=0, m):b(n-1, h))) we will then take into account that summing something again n times is the same as multiplying it by n, and the fact that the second part of the thing being multiplied by n is (n-1) 2^(n-1)/2 as we can always pair the ath last element with the ath first element in the series to produce 2^(n-1) meaning the average is 2^(n-1)/2 for the terms in the series (except for the middle term if there is one, but that will always be the equivalent to (n-1) 2^(n-1)/2 anyways), this is caused by the symmetry of the binomial series (I will leave the meet to you), and there are n-1 terms, we will also be taking into account the fact that 2 2^(n-2)=2^(n-1). Anyways, we can now finally discover the equation f(n)=n (2 n 2^(n-2)-(n-1) 2^(n-2))=n (2 n-n+1) 2^(n-2)=n (n+1) 2^(n-2) so B=n-2, A=n, and hence A+B=n-2+n=2 n-2 and since n=2016, the answer is 2 2016-2=4032-2=4030. I probably made a ridiculous number of grammatical mistakes and I was probably way too vague, but you should be able to get the point if you can read through this onslaught of text.
Problem Loading...
Note Loading...
Set Loading...
Okay time for the combinatorial solution:
Consider the number ways we can choose a committee of k people and nominate two people to be president and chairperson (who are permitted to be the same person). This is just f ( n ) .
Now we count it a different way, which is choosing the president and chairperson first and then choosing the rest of the group. When the chairperson and president are the same we have n 2 n − 1 choices as there are n choices for the president/chairperson, and every other person can either be in the group or not. When the chairperson and president are not the same we have n ( n − 1 ) 2 n − 2 ways of choosing the committee, by a simple count. Adding these together gets n 2 2 n − 2 + n 2 n − 2 .
Now we just sub in n = 2 0 1 6 and get f ( 2 0 1 6 ) = 2 0 1 6 ⋅ 2 0 1 7 ⋅ 2 2 0 1 4 so the answer is 2 0 1 6 + 2 0 1 4 = 4 0 3 0 .